The prevalence of depression and its relationship to health related quality of life among prostate cancer patients in Tertiary Centres, Kuala Lumpur / Mohamad Rodi Isa … [et al.] - Isa, Mohamad Rodi; Foong, Ming Moy; Abdul Razack, Azad Hassan; Mohd Zainuddin, Zulkifli; Zainal, Nur Zuraida (Faculty of Medicine, 2016)
Introduction: To determine the prevalence of depression and its relationship with health related quality of life among prostate cancer patients in tertiary medical centres, Kuala Lumpur. Methods: A hospital-based, cross-sectional study was conducted at the Surgical Clinic, University Malaya Medical Centre and Universiti Kebangsaan Malaysia Medical Centre over a period of fifteen months. Depression level was measured using Depression Anxiety Stress Scale (DASS-21) and the health related quality of life was measured using the Short Form-36 (SF-36). Results: The prevalence of depression was 11.9% (95% CI: 7.0 – 17.0). The total quality of life for non-depression group was 72.30 ± 13.38 and depression group was 54.11 ± 14.59. All the domains in the health related quality of life and coefficient summaries showed significant differences. Univariate analysis showed significant differences in the physical coefficient summary (p < 0.001), mental coefficient summary (p < 0.001) and total quality of life (p = 0.002) among groups with different depression status. In multivariate analysis, the adjusted mean score of the quality of life was associated with age category of the patients (p = 0.012), urinary complaint of hematuria (p = 0.009) and history of orchidectomy (p = 0.023). Conclusions: The prevalence of depression among prostate cancer patients was relatively low. Treatment of the urination and prostate related problems may improve the quality of life among prostate cancer patients with depression.